2012
DOI: 10.1103/physrevd.85.071101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the sensitivity of the air-shower radio signal to the longitudinal shower development

Abstract: We observe a correlation between the slope of radio lateral distributions, and the mean muon pseudorapidity of 59 individual cosmic-ray-air-shower events. The radio lateral distributions are measured with LOPES, a digital radio interferometer co-located with the multi-detector-air-shower array KASCADE-Grande, which includes a muon-tracking detector. The result proves experimentally that radio measurements are sensitive to the longitudinal development of cosmic-ray air-showers. This is one of the main prerequis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Like fluorescence light, the radio signal carries information of the complete longitudinal development of the shower [12]. It is therefore possible to reconstruct X max from the radio signal [13].…”
Section: Introductionmentioning
confidence: 99%
“…Like fluorescence light, the radio signal carries information of the complete longitudinal development of the shower [12]. It is therefore possible to reconstruct X max from the radio signal [13].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally it has been shown that the amplitude of the radio pulse scales with the energy of the primary particle [3]. Recently, it has also been demonstrated that the radio emission pattern observed at the ground is sensitive to the atmospheric depth of shower maximum X max [4,5]. This parameter which depends on the type or mass of the primary particle can be measured with an accuracy comparable to that of established techniques, such as the detection of Fluorescence or Cherenkov light (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…9), but not per individual event, since it depends on the atmospheric depth of the shower maximum [25], and there is no way to reproduce the (unknown) shower maximum of the measured events with the individual simulations. Experimental observation in- Figure 11: Deviation between the measured ǫ100 and the scaled simulated ǫ100 divided by the total uncertainty of the individual events, and a fitted Gaussian for each histogram.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we have decided to use an exponential LDF with an amplitude and a slope parameter, as already in Refs. [24,25] -in particular since a power law as alternative 2-parameter LDF has been shown to be inappropriate for LOPES events [24].…”
Section: Lateral Distribution Function (Ldf)mentioning
confidence: 99%
See 1 more Smart Citation